El marco integrador del control interno como herramienta de cumplimiento del objeto social de empresas bananeras - Bermeo Arce, María Lorena (2015)
This degree work is make due of the need to establish an adequate system of internal control in a company dedicated to the production and marketing of bananas, showing an obstacle to the fulfillment of the objects of the same, given several irregularities by failing to establish an adequate system control to provide security in the various activities carried out. Therefore the Integrated Framework of COSO III Internal Control, by developing its five components of internal control and 17 principles, proposes to the company a reliable tool for regulating the various problems encountered. For the preliminary analysis of this study were used investigative techniques as interview and observation wich served to support the causes of detected inconsistencies.I also was as support different scientific publications that served as an information médium to articulate the importance of establishing internal control structure within each process developed.as a result of this implementation it was displayed positive changes in different áreas of investigación work,achieving this standardize the fulfillment of the proposed objectivies. Suggesting the final term of the present work an innovative proposal to strengthen the control objetives of the company investigated.